PyCO2SYS: marine carbonate system calculations in Python ... - Humphreys, Matthew P.; Sandborn, Daniel; Gregor, Luke; Pierrot, Denis; van Heuven, Steven M. A. C.; Lewis, Ernie R.; Wallace, Douglas W. R. (Zenodo, 2021)
PyCO2SYS is a Python toolbox for solving the marine carbonate system and calculating related seawater properties. Its core is a Python implementation of CO2SYS for MATLAB. Documentation is available at PyCO2SYS.readthedocs.io. Changes in v1.7.0 New features Can now run pyco2.sys with no carbonate system parameter arguments provided, to just return all the equilibrium constants etc. under the specified conditions. Can also run pyco2.sys with only one carbonate system parameter argument. This does not solve the carbonate system, but does calculate all that can be calculated with that parameter. Added carbonic acid constants parameterisation of SB21. Added bisulfate dissociation constant parameterisation of WM13/WMW14. Added spreadsheet-to-spreadsheet function pyco2.ezio (with thanks to Daniel Sandborn). Integrated uncertainty propagation into the main pyco2.sys function and expanded its capabilities. Internal updates Switched default first-guess pH for solving from the alkalinity-carbonate ion parameter pair ...